Peculiarities of Modulating Activity Manifestation of Embryonic Liver Cells on Murine Lymphohemopoietic Complex with Autoimmune Hemolytic Anemia - Gorskaya, A. Yu.; Lutsenko, E. D.; Ostankova, L. V.; Dubrava, T. G.; Goltsev, A. N. (Problems of Cryobiology and Cryomedicine, 2006)
There were summarised the literature data and the results of own investigations on the evaluation of modulating activity of embryonic liver cells (ELCs) on lymphohemopoietic complex (LHPC) of mice with autoimmune hemolytic anemia (AIHA). The analysis of the degree and character of ELCs effect on both total populations of immune-competent cells (ICCs) in thymus, spleen, bone marrow and peritoneal cavity (PC) and on the spleen and thymus organ-specific stromal elements was performed. The data obtained testify to the fact, that the ELCs application is accompanied with the modification of different degree in structural and morphological characteristics of central and peripheral LHPC organs. In respect of specific manifestations of AIHA (autoantibodies accumulation) the ELCs transplantation contributes to a considerable decrease in their content, that can be characterised as the ELCs therapeutic effect manifestation.